ANALISIS BELANJA DAERAH - Wirawan Suhaedi (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2019)
This study aims to determine the financial expenditures performance of the West Lombok Regency for the 2014-2018 period. This research is a descriptive study. The results showed that the expenditures variance in West Lombok Regency in 2014 - 2018 averaged 93.30% in the favorable variance category. The majority of regional expenditure funds are allocated to operational expenditures with an average value of 79.48% while capital expenditures of 20.02%. Budget management is still inefficient with an average expenditure efficiency ratio of 93.30%.